Gendered transitions, career identities and possible selves: the case of engineering graduates. Issue 8 (17th November 2017) - Papafilippou, Vanda; Bentley, Laura
Abstract: This article, drawing upon the Paired Peers project, a longitudinal qualitative study ( n  = 90), examines how seven UK engineering graduates, four women and three men, construct their career identities during the transitionary period from university to work. It explores how gender and the occupational cultures that reside within the sector, and the wider sociocultural context, affect women's careers identities, choices and trajectories. The longitudinal design, characteristics of the cohort and the theoretical framework of possible selves contribute to the originality of this empirical research. In this paper, we show how female graduates gradually adapted their occupational aspirations and career identities to fit with socio-cultural expectations and how they struggled to construct viable 'engineering' selves in the vital career identity development phase of their first years of employment when most female STEM graduates change careers.